Alternative Prey Reduces Largemouth Bass Predation Mortality on Newly Stocked Channel Catfish Fingerlings. (30th July 2021) - Becher, Cory; Tyszko, Stephen M.; Zweifel, Richard D.; Conroy, Joseph D.; Pritt, Jeremy J.; Ludsin, Stuart A.
Abstract: Management agencies commonly stock Channel Catfish Ictalurus punctatus as advanced yearlings instead of fingerlings (age 0) to help reduce potential predation mortality despite uncertainty regarding the degree to which predation limits fingerling poststocking survival. To better understand whether fingerling survival during the first 7 d after stocking—when predation risk is likely greatest—could benefit from the presence of alternative prey fish, we conducted an experiment in 0.4‐ha ponds ( N = 18; 6 ponds/treatment) that measured fingerling (TL range = 56–186 mm) survival in ponds with predators only (adult Largemouth Bass Micropterus salmoides ; mean TL = 327 mm; SE = 21), with predators and alternative prey fishes (Bluegill Lepomis macrochirus and Goldfish Carassius auratu s), or with neither (i.e., control ponds). Without alternative prey, fingerling Channel Catfish survival 1 week after stocking was significantly ( P < 0.01) lower (89%) than in the ponds with alternative prey (98%) or in the control treatment with no predators (97%). Our experiment also indicated the potential for alternative prey to promote fingerling survival by reducing water clarity, not just by serving as a buffer from predation. Further research, however, is needed to determine the degree to which our findings apply to larger ecosystems and to learn whether stocked fingerlings survive well enough after the initial stocking period to achieve desired management goals. Even so, our results suggest that alternative prey can reduce Largemouth Bass predation mortality on fingerlings immediately after stocking, which could influence Channel Catfish stocking approaches in some managed systems.